Erratum: Corrigendum to “New steroidal saponins and antiulcer activity from Solanum paniculatum L.” (Food Chem. (2015) 186 (160–167)) - Vieira Júnior, Gerardo M. [UNESP]; da Rocha, Cláudia Quintino [UNESP]; Rodrigues, Tamires de Souza [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Vilegas, Wagner [UNESP] (Elsevier, 2017)
The authors regret for the change in the article title from “New steroidal saponins and antiulcer activity from Solanum paniculatum L.” to “New steroidal saponin and antiulcer activity from Solanum paniculatum L.”. The compounds 2 and 4 named diosgenin 3-O-β-D-glucopyranosyl(1″ → 6′)-O-β-D-glucopyranoside and diosgenin β-D-glucopiranoside, respectively, will be modified for yamogenin 3-O-β-D-glucopyranosyl(1″ → 6′)-O-β-D-glucopyranoside for 2 and yamogenin β-D-glucopiranoside for 4. These compounds were related with a mistake in the name of the aglycones that were related as DIOSGENIN in the text of “New steroidal saponins and antiulcer activity from Solanum paniculatum L.”, but the correct aglycone is YAMOGENIN. The compound 2 was related as a new compound in the original text, but with this modification, the compound 2 was previously isolated from Solanum torvum and named Torvoside M,1 therefore not being unpublished in literature. The compound 4 was previously isolated from Borassus flabellifer.2 1. Lu, Y., Luo, J., Huang, X., & Kong, L. (2009). Four new steroidal glycosides from Solanum torvum and their cytotoxic activities. Steroids, 74, 96–101.2. Yoshikawa, M., Xu, F., Morikawa, T., Pongpiriyadacha, Y., Nakamura, S., Asao, Y., Kumahara, A., & Matsuda, H. (2007). Medicinal flowers. XII1) New spirostane-type steroid saponins with antidiabetogenic activity from Borassus flabellifer. Chemical Phamacological Bulletin, 55(2), 308–316.Some chemical shifts have been corrected in Table 3. The new table is below. The authors would like to apologise for any inconvenience caused.